PENGARUH PESAN KAMPANYE PUBLIC RELATIONS TERHADAP BRAND IMAGE DI KALANGAN REMAJA WANITA : Survei Kampanye "Halal Dari Awal" oleh Wardah Cosmetics pada mahasiswi di Universitas Islam Negeri Syarif Hidayatullah Jakarta, Fakultas Ilmu Dakwah dan Ilmu Komunikasi Angkatan 2015 - Raihanah Sari, - (2019)
The development of modern-oriented lifestyles and discussing Islamic values can be seen from several social phenomena in society such as more critical communities in assessing halal products to be consumed, one of which is by choosing halal cosmetic products in the midst of the proliferation of outdoor cosmetic products on the market. Through the #HalaldariAwal campaign, Wardah Cosmetics emphasizes the importance of being more selective in choosing halal cosmetic products, especially among teenagers who are just starting out and interested in using cosmetics. The approach used in this study is quantitative. This study aims to measure how much influence the #Halaldariwal campaign message has on Brand Image among young women. The population in this study were students at the Syarif Hidayatullah State Islamic University Jakarta, the 2015 Faculty of Da'wah and Communication Sciences which totaled 299 people. The model used in this study is the Campaign Compound Model. Campaign Message is measured based on two (2) dimensions namely Message Content and Message Structure while Brand Image is measured based on three (3) dimensions namely Image Maker, User Image and Product Image. Correlation test results are known to have a moderate or fairly strong relationship, meaning that the campaign message contained in the #HalaldariAwal campaign can be accepted by students of Syarif Hidayatullah State Islamic University Jakarta, Faculty of Da'wah and Imu Communication Sciences, Class 2015. The effect test results are known to have significant but not significant, because Wardah's brand image is not caused only by the #HalaldariAwal campaign message. The results of the calculation of hypothesis testing with t count can be concluded that Ho is rejected and Ha is accepted